PERENCANAAN BANGUNAN PENAMPUNG AIR SEDERHANA UNTUK KEBUTUHAN MASYARAKAT DI KAMPUNG SINAR HARAPAN - Syaiful Syaiful; Arini Alfan Hasanah; Dinihari Mulya Lestari (Lembaga Penelitian dan Pengabdian kepada Masyarakat UIKA Bogor, 2024)
Several things have an important role in life, one of which is water. Water has various kinds that can be used for various daily needs, one of which is springs that produce clean water, in general, it can be used for washing dishes, washing clothes, bathing or used as drinking water if it goes through the cooking process. Groundwater that comes out by itself to the ground surface and is almost not influenced by the seasons, can be called springs. In Bogor Regency, some villages still use springs for daily activities, these springs are used for 32 people. The village is Sinar Harapan Village. To make it easier for residents to get clean water, we are planning a water reservoir. site survey and data collection of water discharge is the first step to start the research. The water discharge data was collected 3 times using a bucket with a volume of 25 liters and then the water discharge value was 0.257 liters/second. The next step is interviews with residents, interviews are conducted to obtain identification data on water usage patterns that are used to determine peak hours of water use, based on the results of the calculation of water usage patterns, a water storage building is planned with a size of 1.5 m x 2.5 m x 0.75 m and a volume of 2.812 m3.